2020
DOI: 10.5435/jaaos-d-19-00637
|View full text |Cite
|
Sign up to set email alerts
|

Association of State Legislation and Industry Compensation to Orthopaedic Residents: A 3-Year Review of the Centers for Medicare and Medicaid Services Open Payments Database

Abstract: Background: The Sunshine Act aims to increase the transparency of physicians receiving compensation from pharmaceutical and medical device companies. Nine states have supplementary legislation in addition to the Federal Sunshine Act. The purpose of this study is to assess the characteristics of financial compensation to orthopaedic residents on the Centers for Medicare and Medicaid Services (CMS) Open Payments Database in states with more restrictive regulations compared with those without addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Garstka et al 11 determined that industry payments were markedly different in particular states in comparison with others and suggested that state government regulation has played a role in this distribution. Similarly, Wills et al 34 did a study on orthopaedic surgery residents receiving industry payments, showing that residents in least restrictive states were more likely to receive payments than those in more restrictive states. We believe that additional research is needed to determine the factors contributing to the geographic distribution of reported industry payments.…”
Section: Discussionmentioning
confidence: 98%
“…Garstka et al 11 determined that industry payments were markedly different in particular states in comparison with others and suggested that state government regulation has played a role in this distribution. Similarly, Wills et al 34 did a study on orthopaedic surgery residents receiving industry payments, showing that residents in least restrictive states were more likely to receive payments than those in more restrictive states. We believe that additional research is needed to determine the factors contributing to the geographic distribution of reported industry payments.…”
Section: Discussionmentioning
confidence: 98%
“… 13 Industry relationships represent another means of surgeon financial compensation, which is often out of proportion to the small specialty size. 18 …”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the type of medical training may also affect the implant utilization behavior of practicing surgeons. 18 The Orthopaedic Census Survey reported just over 30 000 allopathic orthopedists in the United States at the time of publication in 2018. 26 The American Osteopathic Academy of Orthopedics website reports over 1900 members, with 192 practicing in the Northeast, 422 practicing in the Midwest, 349 practicing in the South, and 201 practicing in the West.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CMS database lists the following categories for which payments are received: consulting fee, royalty and licensing, food and beverage expenditure, travel and lodging, educational speaker payments, noneducational speaker payments, education, grant, entertainment, and gifts. The method employed was comparable with those that have been used in previous CMS studies 16,17 .…”
Section: Methodsmentioning
confidence: 97%